Weather-proof anti-carbonization low-carbon concrete and preparation method thereof

By using combined technologies such as low-carbon composite powder, weather-resistant composite reagents and anti-carbonizing agents in concrete, the problems of carbonization and weather-resistant properties of mineral blended concrete under long-term environmental impacts have been solved, and efficient carbon emission reduction and structural durability have been achieved.

CN119735401APending Publication Date: 2025-04-01CHINA CONSTR WEST CONSTR SOUTHWEST CO LTD +3

Patent Information

Application Number
CN202411902069.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing mineral blended concrete is prone to problems such as reduced carbonization resistance and insufficient weather resistance under long-term environmental influences, resulting in the impact of structural durability and safety.

Method used

A combination of low-carbon composite powder, weather-resistant composite reagents and anti-carbonizing agents is used to prepare a weather-resistant, carbonization-resistant low-carbon concrete. By improving the structural strength, compactness and protective properties of the concrete, it improves its carbonization and weather-resistant properties.

Benefits of technology

Under the influence of long-term external environment, the overall carbonization resistance and weather resistance of concrete have been significantly improved, extending the service life of the structure and reducing carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005203456040000091
    Figure BDA0005203456040000091
Patent Text Reader

Abstract

The invention discloses weather-resistant anti-carbonization low-carbon concrete which is prepared from the following components in parts by mass: 208 to 255 parts of cement, 65 to 78 parts of fly ash, 116 to 156 parts of low-carbon composite powder, 765 to 815 parts of fine aggregate, 1000 to 1075 parts of coarse aggregate, 1.5 to 2.8 parts of composite fiber, 3.0 to 4.2 parts of weather-resistant composite reagent, 4.5 to 6 parts of anti-carbonization agent, 6.5 to 7.8 parts of additive and 148 to 162 parts of water, the low-carbon composite powder comprises red mud powder, high-titanium slag powder and lithium slag powder; the weather-resistant composite reagent comprises polyacrylamide, an organic silicon emulsion and a CaO expanding agent. The concrete disclosed by the invention can still ensure good overall carbonization resistance and weather resistance under the long-term influence of an external environment, can realize resource utilization of various industrial solid waste resources, and has remarkable economic and environmental benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and specifically relates to weather-resistant and carbonation-resistant low-carbon concrete and a preparation method thereof. Background Art

[0002] Since its introduction, cement has been an indispensable part of building materials due to its low price, good performance, and ease of use. However, with the advancement of green and low-carbon buildings, reducing cement usage and reducing carbon emissions from cement production have become important research directions. Using an appropriate amount of highly active mineral admixtures to replace cement to prepare concrete can not only improve the working performance of concrete, but also improve the strength and homogeneity of the concrete structure. At the same time, it can reduce drying shrinkage and creep strain, greatly reduce the dependence of concrete on cement, and reduce carbon emissions. It has strong economic, social and environmental benefits.

[0003] Commonly used mineral admixtures include fly ash, slag, limestone powder, mineral powder, steel slag powder, etc., which are widely used in concrete; however, as the amount of mineral admixtures gradually increases, concrete quality problems have emerged. Excessive addition of mineral admixtures leads to a decrease in the early hydration products of cement, which in turn causes low early strength and reduced density of concrete. On the other hand, the active components SiO2 and Al2O3 in mineral admixtures require alkali to excite the reaction, which will aggravate the consumption of Ca(OH)2 in the gel system and accelerate the carbonization rate. Both effects will lead to a decrease in the concrete's ability to resist CO2 corrosion, and the steel bars inside the concrete will rust due to the loss of the protective layer, resulting in a decrease in the overall durability of its concrete components. In addition, concrete with mineral admixtures has to serve under the long-term effects of various environmental factors such as temperature, humidity, ultraviolet rays and pollutants, and is extremely prone to cracking, spalling, and strength reduction, which seriously affects its service life and safety. Therefore, improving the anti-carbonation and weathering properties of concrete with mineral admixtures has become a hot topic of research.

[0004] At present, there are many studies on the anti-carbonation performance of concrete with mineral admixtures, but there are few studies on its weather resistance. For example, patent application CN117585953A discloses a highly efficient anti-carbonation concrete, which uses an anti-carbonation agent, a reinforcing agent and reinforcing fibers to prepare concrete with excellent compressive properties and high anti-carbonation performance. However, its main purpose is to improve the anti-carbonation performance and compressive strength of concrete, and does not involve the improvement of the service performance of concrete in various environments. In order to meet the growing demand for infrastructure construction, it is of great research and application significance to further develop green and low-carbon concrete and simultaneously solve its carbonation and weather resistance problems. Summary of the invention

[0005] The main purpose of the present invention is to provide a weather-resistant and carbonation-resistant low-carbon concrete in response to the problems and shortcomings of the prior art. The concrete can still ensure good overall carbonation resistance and weather resistance under the long-term influence of the external environment, and can realize the resource utilization of various industrial solid waste resources, with significant economic and environmental benefits.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A weather-resistant and carbonation-resistant low-carbon concrete comprises the following components in parts by weight: 208-255 parts of cement, 65-78 parts of fly ash, 116-156 parts of low-carbon composite powder, 765-815 parts of fine aggregate, 1000-1075 parts of coarse aggregate, 1.5-2.8 parts of composite fiber, 3.0-4.2 parts of weather-resistant composite reagent, 4.5-6 parts of anti-carbonation agent, 6.5-7.8 parts of admixture, and 148-162 parts of water; the low-carbon composite powder comprises red mud powder, high-titanium slag powder and lithium slag powder; the weather-resistant composite reagent comprises polyacrylamide, silicone emulsion and CaO expansion agent.

[0008] In the above scheme, the cement is ordinary Portland cement, 42.5 grade or above, and the residue on 45μm square hole sieve is 5.0-5.4%; the fly ash is Class F II fly ash, with a density of 2.1-2.3g / cm 3 The loss on ignition is 4.7-5.2%.

[0009] In the above scheme, the mass ratio of red mud powder, high titanium slag powder and lithium slag powder in the low carbon composite powder is 1.5:(3.5-5.5):(2.0-3.2).

[0010] Furthermore, the red mud, high-titanium slag and lithium slag are mixed in a planetary mixer for 30 to 45 minutes.

[0011] In the above scheme, the main chemical components of the red mud powder are CaO, Al2O3, SiO2 and Fe2O3, etc. The sum of the contents of CaO, Al2O3, SiO2 and Fe2O3 accounts for more than 85wt% of the total amount of the red mud powder, the median diameter (D50) of the particle size composition is 12.44-14.68μm, and the density is 2.86-2.93g / cm 3 , pH is 12.2~12.6.

[0012] In the above scheme, the TiO2 content in the high-titanium slag powder is 10-15wt%, and its specific surface area is 450-500m 2 / kg.

[0013] In the above scheme, the lithium slag powder is a powder with a porous structure, the sum of the contents of SiO2 and Al2O3 is 75-80wt%, and the specific surface area is 400-450kg / m2 .

[0014] In the above scheme, the fine aggregate is continuously graded limestone machine sand with a size less than 4.75 mm, a fineness modulus of 2.7 to 3.0, a limestone powder content of 8.2 to 9.5%, and a porosity of 36 to 39%.

[0015] In the above scheme, the coarse aggregate is pebbles and crushed stones (including pebbles and crushed stones) with a particle size of 5 to 25 mm, wherein the crushed stones are granite, the mass ratio of pebbles to crushed stones is 1: (1.5 to 2), the overall crushing index is 13 to 15%, and the porosity is 43 to 45%.

[0016] In the above scheme, the composite fiber is a mixture of polypropylene fiber, cellulose fiber and polyvinyl alcohol fiber, and the mass ratio of polypropylene fiber, cellulose fiber and polyvinyl alcohol fiber is (1.6-2.2):(2.5-3.2):1.

[0017] In the above scheme, the average length of the polypropylene fiber and the polyvinyl alcohol fiber in the composite fiber is 1.5 to 2 cm, and the average length of the cellulose fiber is 0.5 to 1 cm; the fiber diameter is 20 to 40 μm.

[0018] In the above scheme, in the weather-resistant composite reagent, the mass ratio of polyacrylamide, silicone emulsion and CaO expansion agent is 1:(2.2-3.5):(6.0-7.2).

[0019] In the above scheme, the molecular weight of the polyacrylamide is 8 to 10 million;

[0020] In the above scheme, the organosilicon emulsion is a colorless transparent liquid, and its effective solid content is 55-65%.

[0021] In the above scheme, the main components of the CaO expansion agent are free calcium oxide (f-CaO), calcium sulfoaluminate (C4A3S) and gypsum (CaSO4), wherein the CaO content is ≥85%.

[0022] In the above scheme, the anti-carbonization agent comprises nano-silicon dioxide, sodium aluminate solution and modified hydrotalcite, and the mass ratio of nano-silicon dioxide, sodium aluminate and modified hydrotalcite is 1:(1.8-2.6):(2.4-3.8).

[0023] In the above scheme, the average particle size of the nano-silicon dioxide is 20-35nm, and the specific surface area is 230-260m 2 / g, density 2.2~2.6g / cm 3 , has good dispersibility and hydrophilicity.

[0024] In the above scheme, the concentration of the sodium aluminate solution is 35-42wt%, the Na2O / Al2O3 molar ratio is 1.48-1.60, and the specific gravity is 1.42-1.49.

[0025] In the above scheme, the specific surface area of ​​the modified hydrotalcite is 29.9 to 35.6 m 2 / g, white powder.

[0026] Furthermore, the modified hydrotalcite is obtained by calcining and stirring natural hydrotalcite powder as the main raw material, and then adding aminobenzoic acid and alkaline solution for modification; the specific steps include: calcining the natural hydrotalcite powder at 480-520° C. for 3-3.5 hours, then cooling to room temperature in an inert atmosphere, then adding 50-55° C., 350-400 ml of warm water for stirring (stirring rate is above 600 r / min, time is 20-30 minutes), cooling to room temperature, then adding aminobenzoic acid and alkaline solution for stirring modification (stirring rate is 200-300 r / min, stirring time is 30-45 minutes), then using an acid solution to adjust the pH of the obtained solution to 9-10, stirring the obtained suspension (8-10 hours), filtering, and vacuum drying (10-12 hours) to obtain the modified hydrotalcite.

[0027] In the above scheme, the mass ratio of the natural hydrotalcite powder, aminobenzoic acid and alkaline solution is 1:(8-10):(3-4.5).

[0028] Furthermore, the alkaline solution may be a NaOH solution or the like, with a concentration of 40 to 50 wt %, and the acid solution may be a HNO 3 solution, with a concentration of 20 to 25 wt %.

[0029] In the above scheme, the admixture is a polycarboxylic acid high-efficiency water reducing agent with a solid content of 12 to 14% and a water reduction rate of 24 to 26%.

[0030] The above-mentioned method for preparing weather-resistant and carbonation-resistant low-carbon concrete comprises the following steps:

[0031] 1) Add the coarse aggregate, cement, fly ash, low carbon composite powder, fine aggregate, composite fiber, admixture and part of water weighed according to the proportion into a mixer in sequence for premixing;

[0032] 2) Then add weather-resistant composite reagent, anti-carbonation curing agent and the remaining amount of water, stir evenly, and obtain weather-resistant and anti-carbonation low-carbon concrete.

[0033] In the above scheme, 1 / 3 to 1 / 2 of the amount of water is added in step 1).

[0034] The weather-resistant and carbonation-resistant low-carbon concrete prepared according to the above scheme has a 28d compressive strength of more than 55.0MPa; a 180d carbonization depth of less than 2.8cm; and a 180d electric flux of less than 650C.

[0035] The principles of the present invention include:

[0036] (1) The present invention uses continuously graded coarse aggregate pebbles-granite crushed stones and limestone fine aggregate as the concrete support skeleton. The mixed use of coarse and fine aggregates of different materials is beneficial to improving the performance of concrete (such as workability, mechanical properties and density, etc.). On the other hand, limestone fine aggregate often carries a certain amount of limestone powder due to the construction process. The limestone powder can not only improve the workability of concrete but also fill in the pores of concrete to improve the density of concrete, thereby improving the weather resistance and anti-carbonation performance of concrete.

[0037] (2) The low-carbon composite powder of the present invention is composed of three solid wastes, namely red mud, high-titanium slag and lithium slag. When red mud is added to concrete, the fluidity of concrete will decrease, the fluidity performance will decrease, and the overall alkalinity of concrete will increase. However, if the amount of red mud added does not exceed the limit, the strength and density of concrete can be improved. High-titanium slag has less glass phase and lower activity, but it can significantly improve the problem of low fluidity of concrete. Lithium slag after extracting lithium mica by salt method contains sodium salt, which is easy to cause structural alkali and corrode steel bars. However, after adding it, it has a promoting effect on the strength of concrete and can significantly improve the appearance of cement hydration products, forming a network structure that is more compact. Under the alkali excitation of red mud, high-titanium slag and lithium slag promote the volcanic ash reaction of amorphous silicon-aluminum phase, produce more C-(A)-SH gel, and greatly improve its potential activity. On the other hand, due to the alkali excitation, the alkalinity brought by the alkalinity of lithium slag and red mud is reduced, the damage to steel bars is reduced, and due to the intensified hydration reaction, the concrete structure is dense, and the harmful substances are solidified inside the building structure, reducing its pollution to the environment. The three particles have different particle sizes and fill each other's pores, working synergistically to improve the fluidity of concrete while increasing the strength and durability of the concrete structure. They are green, low-carbon, and highly efficient.

[0038] (3) The polyacrylamide introduced in the weather-resistant composite reagent can improve the viscosity, carbonation resistance, impermeability and durability of concrete when used alone. On the other hand, polyacrylamide and polycarboxylic acid water reducer work together to reduce calcium hydroxide crystals while improving the fluidity of concrete, and change the morphology of these crystals from large-scale parallel stacking to small-scale edge erosion structure, reducing the pores on the concrete surface and increasing the compactness of the concrete structure. On the one hand, silicone emulsion can increase the initial hydration rate of concrete. It contains a large number of hydroxyl groups, which can effectively couple with the CSH layer, thereby transforming CSH growth into "mesoscale assembly", significantly increasing the average chain length of CSH gel, and accelerating the hydration rate; on the other hand, silicone emulsion can significantly increase the water contact angle of concrete, reduce the water absorption rate of concrete, and then increase the hydrophobicity of concrete, thereby reducing the relative humidity inside the concrete, and effectively delaying the migration process of chloride ions in concrete. CaO expansion agent has good auxiliary performance in concrete. First of all, the expansion effect under effective dosage can offset the shrinkage of concrete during curing, reduce the risk of shrinkage cracking, and reduce the invasion of harmful ions into concrete. On the other hand, the large-scale use of mineral admixtures today has led to the consumption of excessive calcium hydroxide by volcanic ash reaction, and even caused the system to be "calcium deficient", making it easy to carbonize and promote the corrosion of reinforced concrete. Adding CaO expansion agent has a certain "calcium supplement" effect, thereby enhancing the durability of the system. The three chemical reagents improve the performance of concrete from the inside out. The CaO expansion agent reduces the internal shrinkage of concrete and increases the internal alkalinity of concrete; the organosilicon emulsion reduces the internal humidity of concrete and reduces the invasion of harmful ions; polyacrylamide reduces the pores on the surface of concrete and further strengthens the surface density of concrete. The whole synergistic effect significantly improves its weather resistance and anti-carbonization performance in different natural environments from the inside out.

[0039] (4) The anti-carbonation curing agent of the present invention comprises nano-silicon dioxide, sodium aluminate solution and modified hydrotalcite; the introduced nano-silicon dioxide can provide nucleation sites in the hydration process, which is beneficial to improve the cement hydration rate, early strength and volcanic ash reaction activity; on the other hand, the pore size of the cement matrix is ​​refined, which partially inhibits the generation of expansive CaCO3 and changes the structure of CaCO3 crystals; therefore, the available CaCO3 that reacts with carbon dioxide is 2+The addition of sodium aluminate solution increases the hydration reaction rate of concrete and provides certain alkaline conditions, which increases the hydration products and improves its compactness. On the other hand, adding sodium aluminate solution to concrete and dispersing it on the surface of concrete after vibration can significantly reduce the microcracks on its surface. This is because it forms dense hydrocalcium zeolite and sodium magnesium magnesia on the surface with cement paste, which reduces the drying shrinkage and CO2 permeability of concrete, thereby improving its carbonization performance. The present invention uses aminobenzoic acid and the like to improve hydrotalcite, and the resulting modified hydrotalcite has both CO3 2- The ions also contain some aminobenzoic acid anions. On the one hand, they can have a good adsorption effect on CO2. After adsorbing carbonate ions, they recrystallize, the interlayer spacing decreases, and more active sites are added, providing more opportunities for CO2 capture, thereby improving the concrete's carbonation resistance. On the other hand, the modified hydrotalcite plays a dual role in chloride-induced corrosion: it captures chloride and releases inhibitory anions to protect the steel bars from corrosion, thereby improving the concrete's carbonation resistance and corrosion resistance. The three chemical reagents can improve density, increase strength and absorb CO2, Cl - The three aspects can improve the carbonation resistance and weather resistance of concrete, and their synergistic effect can significantly improve the various properties of concrete.

[0040] (5) The several fibers used in the present invention can comprehensively improve the compactness, compressive strength, carbonation resistance, crack resistance, shrinkage and frost resistance of concrete. On the other hand, the fibers are combined with nano-silicon dioxide and modified hydrotalcite. The hydration products of nano-particles and cement particles are attached to the surface and interior of the fibers and modified hydrotalcite, making the bonding between them tighter. During the carbonization process, the fibers can play a pulling role to prevent carbonization shrinkage cracks, and use the surface hydration products to resist the acidic environment, further improving the utilization efficiency of the fibers.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] 1) The weather-resistant and carbonation-resistant low-carbon concrete of the present invention can realize the large-volume application of various industrial solid wastes, reduce carbon emissions, and has strong economic and environmental benefits;

[0043] 2) The present invention uses cement, fly ash, and low-carbon composite powder as main raw materials, and further combines weather-resistant composite reagents and anti-carbonization agents, which can take into account good mechanical properties, overall anti-carbonization properties, and weathering properties, and effectively broaden the application scope of concrete;

[0044] 3) The preparation method of the present invention is relatively simple, low in cost, and suitable for popularization and application. DETAILED DESCRIPTION

[0045] The technical solution of the present invention will be fully and clearly described below in conjunction with specific embodiments, but the described embodiments are only some embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0046] In the following examples, the red mud used is industrial solid waste red mud discharged from the process of producing alumina by sintering method, and its main chemical components are CaO (48%), Al2O3 (6%), SiO2 (22%) and Fe2O3 (9%), etc. The median diameter (D50) of the particle size composition is 13.567 μm, and the density is 2.89 g / cm 3 , pH is 12.6.

[0047] The high-titanium slag used is the water-quenched high-titanium slag produced after smelting pig iron from vanadium-titanium magnetite. After crushing and grinding, the specific surface area is 480m 2 / kg of fine powder; wherein the TiO2 content is 12wt%.

[0048] The lithium slag used is a solid waste generated in the process of producing lithium salt from lepidolite ore. It is a porous powder with a total content of SiO2 and Al2O3 of 80%. After drying and grinding, the specific surface area is 435kg / m 2 Lithium slag powder used.

[0049] The fine aggregate used is continuously graded limestone machine sand with a size of less than 4.75mm, a fineness modulus of 2.7, a limestone powder content of 8.2%, and a porosity of 38%; the coarse aggregate is pebbles and crushed stones with a particle size of 5 to 25mm. The crushed stones are granite, and the mass ratio of pebbles to crushed stones is 1:1.5. The overall crushing index is 13% and the porosity is 43%.

[0050] The average length of the polypropylene fiber and the polyvinyl alcohol fiber used is 1.5 cm, and the average length of the cellulose fiber is 0.5 cm.

[0051] The polyacrylamide used is a white, water-soluble solid powder pure chemical reagent with a molecular weight of 8.6 million; the silicone emulsion is a commercially available octyltriethoxysilane oligomer emulsion, a colorless and transparent liquid with an effective solid content of 62%.

[0052] The main component of CaO expansion agent is free calcium oxide (f-CaO), with a small amount of calcium sulfoaluminate (C4A3S) and gypsum (CaSO4), of which the CaO content is 87%.

[0053] The average particle size of the nano-silicon dioxide used is 20nm and the specific surface area is 230m 2 / g, density 2.4g / cm 3, with good dispersibility and hydrophilicity; the concentration of sodium aluminate solution is 40wt%, the molar ratio (Na2O / Al2O3) is 1.56, and the specific gravity is 1.49.

[0054] The specific surface area of ​​the modified hydrotalcite used is 29.9m 2 / g, white powder, the specific preparation steps include: the specific steps include: calcining 5g of natural hydrotalcite powder at 500℃ for 3h, then cooling to room temperature in N2 atmosphere, adding into 50℃, 350ml of warm water with stirring (stirring rate is above 750r / min, time is 30min), cooling to room temperature, then adding 45g of aminobenzoic acid and 20g of 40wt% NaOH solution for modification (45min), then using 22wt% HNO3 solution to adjust the pH value of the obtained solution to 10, stirring the obtained suspension (10h), filtering and vacuum drying (12h), and obtaining the modified hydrotalcite.

[0055] The admixture used is polycarboxylic acid high-efficiency water-reducing agent with a solid content of 12% and a water-reducing rate of 26%.

[0056] Example 1

[0057] A weather-resistant and carbonation-resistant low-carbon concrete, the preparation method of which comprises the following steps:

[0058] 1) Weigh the raw materials; the raw materials and their weight proportions are: 210 parts of cement, 65 parts of fly ash, 120 parts of low-carbon composite powder, 765 parts of fine aggregate, 1000 parts of coarse aggregate, 1.5 parts of composite fiber, 3.0 parts of weather-resistant composite reagent, 4.7 parts of anti-carbonization curing agent, 6.5 parts of admixture, and 149 parts of water;

[0059] Among them, the mass ratio of red mud powder, high titanium slag powder and lithium slag powder in low carbon composite powder is 1.5:3.6:2.2; the mass ratio of polypropylene fiber, cellulose fiber and polyvinyl alcohol fiber in composite fiber is 1.7:2.6:1; the mass ratio of polyacrylamide, silicone emulsion and CaO expansion agent in weather-resistant composite reagent is 1:2.4:6.2; the mass ratio of nano-silica, sodium aluminate solution and modified hydrotalcite in anti-carbonization curing agent is 1:1.8:2.5;

[0060] 2) Add the coarse aggregate, cement, fly ash, low carbon composite powder, fine aggregate, composite fiber, admixture and half of the water weighed according to the proportion into a clean mixer and premix for 1 minute (stirring speed is 45 / min);

[0061] 3) Then add the weighed weather-resistant composite reagent, anti-carbonation curing agent and the remaining amount of water into the mixer, continue stirring for 3 minutes (stirring rate is 45 / min), stir and mix evenly and then pour out to obtain weather-resistant and anti-carbonation low-carbon concrete.

[0062] Example 2

[0063] A weather-resistant and carbonation-resistant low-carbon concrete, the preparation method of which is roughly the same as that of Example 1, except that it includes the following components in weight parts: 230 parts of cement, 70 parts of fly ash, 135 parts of low-carbon composite powder, 790 parts of fine aggregate, 1040 parts of coarse aggregate, 2.1 parts of composite fiber, 3.6 parts of weather-resistant composite agent, 5.4 parts of anti-carbonation curing agent, 7 parts of admixture, and 155 parts of water.

[0064] Among them, the mass ratio of red mud powder, high-titanium slag powder and lithium slag powder in the low-carbon composite powder is 1.5:4.7:2.8; the mass ratio of polypropylene fiber, cellulose fiber and polyvinyl alcohol fiber in the composite fiber is 1.9:2.8:1; the mass ratio of polyacrylamide, silicone emulsion and CaO expansion agent in the weather-resistant composite reagent is 1:2.6:6.7; the mass ratio of nano-silica, sodium aluminate solution and modified hydrotalcite in the anti-carbonization curing agent is 1:2.1:3.2.

[0065] Example 3

[0066] A weather-resistant and carbonation-resistant low-carbon concrete, the preparation method of which is substantially the same as that of Example 1, except that it comprises the following components in parts by weight:

[0067] 252 parts of cement, 76 parts of fly ash, 152 parts of low-carbon composite powder, 815 parts of fine aggregate, 1075 parts of coarse aggregate, 2.7 parts of composite fiber, 4.2 parts of weather-resistant composite agent, 6.0 parts of anti-carbonation curing agent, 7.6 parts of admixture, and 161 parts of water;

[0068] Among them, the mass ratio of red mud powder, high-titanium slag powder and lithium slag powder in the low-carbon composite powder is 1.5:5.4:3.2; the mass ratio of polypropylene fiber, cellulose fiber and polyvinyl alcohol fiber in the composite fiber is 2.2:3.1:1; the mass ratio of polyacrylamide, silicone emulsion and CaO expansion agent in the weather-resistant composite reagent is 1:3.3:7.2; the mass ratio of nano-silica, sodium aluminate solution and modified hydrotalcite in the anti-carbonization curing agent is 1:2.6:3.7.

[0069] Blank Group

[0070] A concrete, the preparation method of which is substantially the same as that of Example 2, except that: no low-carbon composite powder, composite fiber, weather-resistant composite agent and anti-carbonation curing agent are added, the amount of cement is adjusted to 365 parts, and other components and preparation process remain unchanged.

[0071] Comparative Example 1

[0072] A concrete, the preparation method of which is substantially the same as that of Example 2, except that: no low-carbon composite powder is added, the amount of cement is adjusted to 365 parts, and other components and preparation process remain unchanged.

[0073] Comparative Example 2

[0074] A concrete, the preparation method of which is substantially the same as that of Example 2, except that the coarse aggregate is replaced with a single limestone aggregate, and the other components and preparation process remain unchanged.

[0075] Comparative Example 3

[0076] A carbonation-resistant low-carbon concrete, the preparation method of which is substantially the same as that of Example 2, except that no weather-resistant composite reagent is added, and other components and preparation processes remain unchanged.

[0077] Comparative Example 4

[0078] A weather-resistant low-carbon concrete, the preparation method of which is substantially the same as that of Example 2, except that no anti-carbonation curing agent is added, and other components and preparation process remain unchanged.

[0079] Comparative Example 5

[0080] A weather-resistant and carbonation-resistant low-carbon concrete, the preparation method of which is substantially the same as that of Example 2, except that the modified hydrotalcite in the anti-carbonation curing agent component is replaced with calcined unmodified hydrotalcite, and the other components and preparation process remain unchanged.

[0081] Comparative Example 6

[0082] Based on Example 2, the materials in the weather-resistant composite reagent are changed to polyacrylamide, silicone emulsion and MgO-type expansion agent, and the mass ratio of the three is the same as the three materials in Example 2, and the other components and preparation process remain unchanged.

[0083] Application Examples

[0084] The above-mentioned Examples 1-3, blank groups and comparative examples 1-5 were used to prepare weather-resistant and carbonation-resistant low-carbon concrete. The curing work of the concrete test blocks was divided into two types. The antifreeze performance test pieces and the sulfate resistance test pieces were tested after standard curing to simulate the freeze-thaw process and the dry-wet process; the remaining test pieces were placed in a natural environment (subjected to natural weather such as solar radiation, rain, and strong wind) for 180 days after standard curing for 28 days, and then relevant tests were carried out. The performance tests included compressive strength, carbonation resistance, chloride ion penetration resistance and cracking performance.

[0085] Anti-freeze performance and resistance to sulfate erosion: The test was carried out in accordance with the national standard GB / T 50082-2009 "Standard for test methods for long-term performance and durability of ordinary concrete". The size of the concrete specimen was 100mm×100mm×100mm. The anti-freeze performance test adopted the quick freezing method and was characterized by the number of anti-freeze times; resistance to sulfate erosion was characterized by the number of dry-wet cycles under sulfate erosion.

[0086] Compressive strength: Concrete is tested in accordance with the national standard GB / T 50107-2010 "Concrete Strength Test and Assessment Standard". The size of the concrete specimen is 100mm×100mm×100mm, and the size conversion coefficient is 0.95.

[0087] Anti-carbonation performance: The test was carried out in accordance with the national standard GB / T 50082-2009 "Standard for test methods of long-term performance and durability of ordinary concrete". The size of the concrete specimen was 400mm×100mm×100mm, and the anti-carbonation performance was characterized by the carbonization depth.

[0088] Chloride ion penetration resistance: The test is carried out in accordance with the electric flux method of the national standard GB / T 50082-2009 "Standard for test methods of long-term performance and durability of ordinary concrete". The size of the concrete specimen is a cylindrical specimen with a diameter of 100±1mm and a height of 50±2mm.

[0089] Cracking performance: A concrete specimen was prepared using a mold with a size of 400 mm × 200 mm × 400 mm, and a camera was used to take pictures of the surface to check whether there were cracks.

[0090] Among them, S-28d refers to the specimen with standard curing for 28 days, and SN-180d refers to the specimen with standard curing for 28 days and then natural curing for 180 days. At the standard curing time of 28 days, the concrete is basically not carbonized, so the carbonization depth is -. The weather resistance is mainly characterized by frost resistance, sulfate corrosion resistance, compressive strength, carbonization resistance, chloride ion penetration resistance and cracking resistance.

[0091] Table 1 Performance parameters of weather-resistant and carbonation-resistant low-carbon concrete

[0092]

[0093] From the analysis of the weathering and carbonization-resistant low-carbon concrete performance test results in Table 1, we can see that:

[0094] (1) By comparing Examples 1-3, it can be seen that the various properties of concrete first increase and then decrease with the increase of each component, but it is also obviously better than the control group of Comparative Example 1, especially the various properties of the weather-resistant and carbonized low-carbon concrete of Example 2 are the best, which shows that when the dosage of each component is small, the various properties of the weather-resistant and carbonized low-carbon concrete increase with the increase of the dosage; when the component mix proportion dosage reaches a certain point, the performance of the weather-resistant and carbonized low-carbon concrete will gradually decrease if the dosage of each component is increased. On the one hand, the reason is that the excessive dosage leads to the decrease of the hydration performance of the concrete itself, the increase of the porosity, and then the decrease of the mechanical properties, carbonization resistance and weather resistance; on the other hand, the reason is that after the dosage of each component is increased, it cannot be evenly dispersed inside the concrete, which not only cannot improve the performance of the concrete, but even has a negative impact on it, so the mix proportion components of the weather-resistant and carbonized low-carbon concrete need to be paid attention to. Overall, the weather-resistant and carbonized low-carbon concrete of Example 2 has excellent performance and can be widely used in engineering construction.

[0095] (2) Comparing Example 2, the blank group and Comparative Examples 1-6, when the addition of low-carbon composite powder, composite fiber, weather-resistant composite agent and anti-carbonation curing agent is cancelled, the antifreeze performance and sulfate corrosion resistance of concrete are significantly reduced, and the initial mechanical properties of concrete are relatively high, but the compressive strength after 180 days of natural environment curing is reduced, the carbonation depth is increased, the electric flux is increased, and cracks appear on the surface, which shows that under the ordinary concrete ratio, the various properties of concrete will be significantly reduced after long-term curing in the natural environment; when only the low-carbon composite powder is cancelled, the various properties of concrete are improved compared with the blank group, but the various properties of comparative Example 2 are significantly reduced, but the initial compressive strength is reduced, which shows that the low-carbon composite powder mainly plays a role in improving the strength of concrete, and has a general effect on improving weather resistance and carbonation performance; when the coarse aggregate is replaced by a single limestone aggregate, the compressive strength and weather resistance of concrete are reduced, and the carbonation depth is increased, but the change range is not large, indicating that the density of concrete with the same aggregate will be improved, thereby causing the various properties of concrete to decrease, but the impact is small; when the weather-resistant composite powder is not added, the concrete is not as dense as the concrete, and the concrete is not as dense as the concrete. When the weather-resistant composite reagent and anti-carbonation curing agent were added, the frost resistance and sulfate erosion resistance of weather-resistant and carbonized low-carbon concrete were significantly reduced, the compressive strength was reduced, and the strength decreased significantly after 180 days, the carbonation depth was deepened, and the electric flux was improved. This shows that the weather-resistant composite reagent and anti-carbonation curing agent have a significant effect on the mechanical properties, weather resistance and carbonation properties of concrete. After cancellation, the various properties of concrete will be significantly reduced; when the modified hydrotalcite in the anti-carbonation agent is changed to unmodified hydrotalcite, the synergistic effect between the three is broken, the compressive strength is reduced, and the strength after 180 days is reduced. The results show that the modified hydrotalcite has a significant improvement effect on the weathering resistance of concrete, and only improves the anti-carbonation performance before modification; when the CaO expansion agent in each component of the weather-resistant composite reagent is replaced by MgO expansion agent, the compressive strength, overall weathering resistance and anti-carbonation performance of concrete are all reduced under its action, indicating that the effect of MgO expansion agent on improving various properties of concrete is worse than that of CaO expansion agent, and the synergistic effect between the three weather-resistant composite reagents in the present invention is the best.

[0096] The concrete prepared by the present invention has excellent weather resistance and carbonization resistance, and has good application value in engineering practice. On the other hand, it uses solid waste, plays a positive role in the recycling and reuse of industrial solid materials, and has a significant effect on energy conservation and emission reduction, green and sustainable development in the construction industry.

[0097] The above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, so the obvious changes or modifications derived are still within the protection scope of the invention.

Claims

1. A weather-resistant and carbonation-resistant low-carbon concrete, characterized in that: The invention comprises the following components in parts by weight: 208 to 255 parts of cement, 65 to 78 parts of fly ash, 116 to 156 parts of low-carbon composite powder, 765 to 815 parts of fine aggregate, 1000 to 1075 parts of coarse aggregate, 1.5 to 2.8 parts of composite fiber, 3.0 to 4.2 parts of weather-resistant composite reagent, 4.5 to 6 parts of anti-carbonization agent, 6.5 to 7.8 parts of admixture, and 148 to 162 parts of water; the low-carbon composite powder comprises red mud powder, high-titanium slag powder and lithium slag powder; the weather-resistant composite reagent comprises polyacrylamide, silicone emulsion and CaO expansion agent.

2. The weather-resistant and carbonation-resistant low-carbon concrete according to claim 1, characterized in that: The cement is ordinary Portland cement, 42.5 grade or above, with a 45 μm square hole sieve residue of 5.0-5.4%; the fly ash is Class F II fly ash, with a density of 2.1-2.3 g / cm 3 The loss on ignition is 4.7-5.2%.

3. The weather-resistant and carbonation-resistant low-carbon concrete according to claim 1, characterized in that: The mass ratio of red mud powder, high titanium slag powder and lithium slag powder in the low carbon composite powder is 1.5:(3.5-5.5):(2.0-3.2).

4. The weather-resistant and carbonation-resistant low-carbon concrete according to claim 1, characterized in that: The sum of the contents of CaO, Al2O3, SiO2 and Fe2O3 in the red mud powder is more than 85wt%, the median diameter is 12.44-14.68μm, and the density is 2.86-2.93g / cm 3 , pH value is 12.2~12.

6.

5. The weather-resistant and carbonation-resistant low-carbon concrete according to claim 1, characterized in that: The TiO2 content in the high-titanium slag powder is 10-15wt%, and its specific surface area is 450-500m 2 / kg; the sum of the contents of SiO2 and Al2O3 in the lithium slag powder is 75-80wt%, and the specific surface area is 400-450kg / m 2 .

6. The weather-resistant and carbonation-resistant low-carbon concrete according to claim 1, characterized in that: The fine aggregate is continuously graded limestone machine sand with a size less than 4.75 mm, a fineness modulus of 2.7-3.0, a limestone powder content of 8.2-9.5%, and a void ratio of 36-39%; the coarse aggregate is gravel with a particle size of 5-25 mm, an overall crushing index of 13-15%, and a porosity of 43-45%.

7. The weather-resistant and carbonation-resistant low-carbon concrete according to claim 1, characterized in that: In the weather-resistant composite reagent, the mass ratio of polyacrylamide, silicone emulsion and CaO expansion agent is 1:(2.2-3.5):(6.0-7.2).

8. The weather-resistant and carbonation-resistant low-carbon concrete according to claim 1, characterized in that: The anti-carbonization agent comprises nano-silicon dioxide, sodium aluminate solution and modified hydrotalcite, and the mass ratio of nano-silicon dioxide, sodium aluminate and modified hydrotalcite is 1:(1.8-2.6):(2.4-3.8).

9. The weather-resistant and carbonation-resistant low-carbon concrete according to claim 8, characterized in that: The modified hydrotalcite is prepared by taking natural hydrotalcite powder as the main raw material, calcining, stirring with warm water, and then adding aminobenzoic acid and alkaline solution for modification.

10. The method for preparing weather-resistant and carbonation-resistant low-carbon concrete according to any one of claims 1 to 9, characterized in that: The steps include: 1) Add the coarse aggregate, cement, fly ash, low carbon composite powder, fine aggregate, composite fiber, admixture and part of water weighed according to the proportion into a mixer in sequence for premixing; 2) Then add weather-resistant composite reagent, anti-carbonation curing agent and the remaining amount of water, stir evenly, and obtain weather-resistant and anti-carbonation low-carbon concrete.

Citation Information

Patent Citations

  • Efficient anti-carbonization concrete and preparation method thereof

    CN117585953A

Cited By

  • Composite modified carbonization-resistant agent, carbonization-resistant super-sulfate cement material as well as preparation process and application of carbonization-resistant super-sulfate cement material

    CN122464631A